Digital media and political engagement worldwide : a comparative study - Anduiza Perea, Eva.; Jensen, Michael James; Jorba, Laia. (New York : Cambridge University Press, 2012)
"This book explores how digital media use affects political attitudes and behavior, and how this relationship is shaped by political environments across countries"--
"This book focuses on the impact of digital media use for political engagement across varied geographic and political contexts, using a diversity of methodological approaches and datasets. The book addresses an important gap in the contemporary literature on digital politics, identifying context dependent and transcendent political consequences of digital media use. While the majority of the empirical work in this field has been based on studies from the United States and United Kingdom, this volume seeks to place those results into comparative relief with other regions of the world. It moves debates in this field of study forward by identifying system-level attributes that shape digital political engagement across a wide variety of contexts. The volume brings together research and scholars from North America, Europe, Latin America, the Middle East, and Asia. The evidence analyzed across the fifteen cases considered in the book suggests that engagement with digital environments influences users' political orientations and that contextual features play a significant role in shaping digital politics"--
1. Introduction Michael J. Jensen, Laia Jorba and Eva Anduiza; 2. The impact of digital media on citizenship in a global perspective Laia Jorba and Bruce Bimber; 3. Recent shifts in the relationship between the Internet and democratic engagement in Britain and the United States Andrew Chadwick; 4. Political engagement and the Internet in the 2008 U.S. presidential elections: a panel survey Allison Hamilton and Caroline J. Tolbert; 5. Online political participation in the United States and Spain Michael J. Jensen and Eva Anduiza; 6. Internet use and political attitudes in Europe Clelia Colombo, Carol Galais, and Aina Gallego; 7. Digital media and offline political participation in Spain Marta Cantijoch; 8. Online participation in Italy: contextual influences and political opportunities Cristian Vaccari; 9. On the causal nature of the relationship between Internet access and political engagement: evidence from German panel data Martin Kroh and Hannes Neiss; 10. The uses of digital media for contentious politics in Latin America Yanina Welp and Jonathan Wheatley; 11. Opening closed regimes: civil society, information infrastructure, and political Islam Muzammil M. Hussain and Philip N. Howard; 12. Digital media and political attitudes in China Min Tang, Laia Jorba, and Michael J. Jensen; 13. Conclusions Laia Jorba, Michael J. Jensen, and Eva Anduiza.
Includes bibliographical references (pages 253-282) and index.
Includes bibliographical references and index
Keywords: Political participation -- Technological innovations -- Cross-cultural studies; Communication in politics -- Technological innovations -- Cross-cultural studies; POLITICAL SCIENCE / General; Internet -- Political aspects -- Cross-cultural studies